A novel HfNbTaTiV high-entropy alloy of superior mechanical properties designed on the principle of maximum lattice distortion. (20th July 2021) - An, Zibing; Mao, Shengcheng; Liu, Yinong; Wang, Li; Zhou, Hao; Gan, Bin; Zhang, Ze; Han, Xiaodong
Graphical abstract: Highlights: A novel single-phase high entropy alloy HfNbTaTiV was created based on the principle of maximum lattice distortion. A combination of yield strength (1.35 GPa) and compressive strain (>45 %) at room temperature is achieved. It exhibit large ductility of >35 % combined with a high yield strength of 720 MPa at 700 °C. The HfNbTaTiV alloy has large lattice distortion, resulting in a high solid solution strengthening of 1094 MPa. Abstract: This paper reports a synergistic design of high-performance BCC high-entropy alloy based on the combined consideration of the principles of intrinsic ductility of elements, maximum atomic size difference for solid solution strengthening and the valence electron concentration criterion for ductility. The single-phase BCC HfNbTaTiV alloy thus designed exhibited a high compressive yield strength of 1350 MPa and a high compressive ductility of >45 % at the room temperature. This represents a 50 % increase in yield strength relative to a HfNbTaTiZr alloy. This is attributed to the maximized solid solution strengthening effect caused by lattice distortion, which is estimated to be 1094 MPa. The alloy was also able to retain 53 % of its yield strength and 77 % of its ductility at 700 °C. These properties are superior to those of most refractory BCC high-entropy alloys reported in the literature.